Benign Metastasizing Leiomyoma of the Lung with Spontaneous Pneumothorax - Okabe, Ryo; Shoji, Tsuyoshi; Huang, Cheng-long (The Thoracic and Cardiovascular Surgeon Reports, 2013)
A 47-year-old woman was admitted with recurrent pneumothorax. Preoperative chest computed tomography (CT) showed multiple lung nodules and cysts bilaterally. She had undergone enucleatic myomectomy 12 years earlier. Video-associated thoracoscopic biopsy was performed. Histopathologically, there were bulla-like dilated cystic changes, the walls of which showed spindle cell proliferation, causing pneumothorax. Hormone therapy was started after benign metastasizing leiomyoma resection; pneumothorax has not recurred in 7 months. Multiple residual lung nodules have decreased or disappeared on CT.
Keywords: benign metastasizing leiomyoma; pneumothorax